ANALISIS YURIDIS TERHADAP PENCEMARAN UDARA AKIBAT PEMBAKARAN SAMPAH TERBUKA DI PERMUKIMAN KABUPATEN BANYUMAS DALAM PERSPEKTIF HUKUM LINGKUNGAN - Nana Semba Dwi Purwana; Eti Mul Erowati; Wiwin Muchtar Wiyono; Elly Kristiani Purwendah (Ganesha Law Review, 2026)
Air pollution caused by open burning of waste in residential areas remains a serious environmental issue in Indonesia, including in Banyumas Regency. This practice generates hazardous emissions that not only degrade air quality but also negatively impact public health and the overall environment. This study aims to analyze environmental legal regulations and the effectiveness of law enforcement regarding air pollution caused by open waste burning in residential areas of Banyumas Regency from an environmental law perspective. This research employs a normative legal method with statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary sources analyzed through qualitative normative analysis. The findings indicate that regulations prohibiting open waste burning are clearly stipulated in Law No. 32 of 2009 on Environmental Protection and Management and Law No. 18 of 2008 on Waste Management. However, in practice, law enforcement remains ineffective due to weak supervision, low public legal awareness, and limited waste management facilities at the local level. Therefore, stronger law enforcement, improved waste management infrastructure, and continuous environmental legal education for the community are required to minimize air pollution.